On Prophecy, Dreams and Human Imagination Synesius, De insommniis - Russell, Donald A.; Nesselrath, Heinz-Günther (SAPERE, 2014)
Synesius' essay De insomniis ('On Dreams') inquires into the meaning and importance of dreams for human beings and treats themes - most of all the relationship of humans to higher spheres -, which for religiously- and philosophically-minded people are still important today.